Decolonizing Faculty Governance at Hispanic Serving Institutions. (July 2023) - Villarreal Sosa, Leticia; Garcia, Gina A.; Bucher, Jacob
While there has been an emphasis within the Hispanic Serving Institution (HSI) literature on decentralizing university governance to allow for antiracist decision-making, there has been less focus on the lack of inclusive representation within faculty governance, particularly for historically excluded groups. Guided by testimonio as methodology and examples from our lived experiences within one small Catholic HSI, we offered five tenets of a decolonized faculty governance structure that democratizes faculty participation in decision-making at HSIs.